యాభై సంవత్సరాల జ్ఞాపకాలు - Rao, Devulapalli Ramanuja (Andhra Saraswata Parishath, 2015)
This book is about briefing about author's experiences in Telugu literary world
Yabhai Samvatsarala Jnapakalu
Keywords: Telugu; యాభై సంవత్సరాల జ్ఞాపకాలు; Yabhai Samvatsarala Jnapakalu; Literature; Telugu; Telugu